Adolescent Pregnant Mother's Health Seeking Practice Using Whatsapp During Covid-19 Pandemic In Indonesia: A Qualitative Analysis Of An Open-Ended Questionnaire Among Pregnant Adolescents - Siti Khuzaiyah; Khadizah Abdul Mumin; Sarena Hashim (Jurnal Ilmiah Kesehatan, 2023)
Adolescents pregnant mothers can potentially have a problem related to their immature physics and psychology. Their health-care-seeking practice is essential to ensure that adolescent pregnant mothers receive adequate care during their pregnancy. During the COVID-19 pandemic, online media should be perceived as an alternative way to help adolescents seek care during pregnancy. This study aimed to explore the experiences of pregnant adolescent mothers who had practiced health-care seeking and followed online counseling using WhatsApp groups. This qualitative survey recruited 16 Indonesian pregnant mothers aged 15-19 who had followed WhatsApp online counseling. An open-ended questionnaire was used to collect data, which were analyzed using thematic content analysis. There were three themes related to pregnant adolescent care-seeking practices using WhatsApp groups: experience, benefits, and advice and hope. The experience had three sub-theme: present experiences, previous experiences, and hindering factors.  The benefits had sub-themes: benefits of WhatsApp counseling and benefits  of Group WhastApp. Their hopes and advices were:  no advice, be polite, be consistent, be patient, and be duplicated by others. Adolescent pregnant mothers had good experiences in practicing health-care seeking using WhatsApp groups. They were more enthusiastic about following the counseling process and found beneficial information and solution regarding their problem during pregnancy. The findings show that providing WhatsApp groups for adolescent pregnant mothers could benefit them.